Opportunities of Organization of Classes in Foreign Languages by Means of Microsoft Teams (in Practice of Teaching Ukrainian as Foreign Language - Hrytsenko, O. V.; Zozulia, I.; Kushnir, I.; Aleksieienko, T.; Stadnii, A.; Гриценко, Ольга Вікторівна (My University, 2024)
The characteristic aspects of learning a foreign language require special resources and tools for online learning. Criteria for choosing educational platforms depend on key elements of an academic subject area. Microsoft Teams (hereafter, MT) educational platform is competitive one because it meets most of the needs that arise during the formation of a secondary linguistic persona. Due to the large number of corporate programs, there are a successful acquisition of language skills and the implementation of all types of oral activities of students. A significant MT advantage is the constant analysis and monitoring of the platform of participants’ needs in the educational process by developers. The article highlights MT advantages and disadvantages. The attention is drawn to individual programs, which, in the authors’ opinion, are the most successful to learn writing, reading, speaking, listening, as well as organize classes that meet needs of modern foreign students.
Keywords: microsoft Teams learning platform; distance learning; blended learning; speaking; reading; writing; listening; interactive exercises